Duration of Exposure Among Close Contacts of Patients With Infectious Tuberculosis and Risk of Latent Tuberculosis Infection. (11th February 2020) - Reichler, Mary R; Khan, Awal; Yuan, Yan; Chen, Bin; McAuley, James; Mangura, Bonita; Sterling, Timothy R
Abstract: Background: Predictors of latent tuberculosis infection (LTBI) among close contacts of persons with infectious tuberculosis (TB) are incompletely understood, particularly the number of exposure hours. Methods: We prospectively enrolled adult patients with culture-confirmed pulmonary TB and their close contacts at 9 health departments in the United States and Canada. Patients with TB were interviewed and close contacts were interviewed and screened for TB and LTBI during contact investigations. Results: LTBI was diagnosed in 1390 (46%) of 3040 contacts, including 624 (31%) of 2027 US/Canadian-born and 766 (76%) of 1013 non-US/Canadian-born contacts. In multivariable analysis, age ≥5 years, male sex, non-US/Canadian birth, smear-positive index patient, and shared bedroom with an index patient ( P < .001 for each), as well as exposure to >1 index patient ( P < .05), were associated with LTBI diagnosis. LTBI prevalence increased with increasing exposure duration, with an incremental prevalence increase of 8.2% per 250 exposure hours ( P < .0001). For contacts with <250 exposure hours, no difference in prevalence was observed per 50 exposure hours ( P = .63). Conclusions: Hours of exposure to a patient with infectious TB is an important LTBI predictor, with a possible risk threshold of 250 hours. More exposures, closer exposure proximity, and more extensive index patient disease were additional LTBI predictors. Abstract : Hours of exposure to an infectious tuberculosis patient is an important predictor of latent tuberculosis infection among close contacts, with an incremental prevalence increase of 8.2% per 250 exposure hours; more exposures, closer exposure proximity, and extensive index patient disease were additional predictors.